Dental implants in individuals living with HIV-1: Results from a prospective study in patients undergoing highly active antiretroviral therapy - Vidal, Fábio; Peres, Rafael Vidal; de Souza, Rodrigo Carvalho; Gonçalves, Cristiane; Pavan, Priscila; Gonçalves, Lucio Souza (Special care in dentistry, 2022)
To assess survival and success rates of dental implants and the occurrence of peri-implant diseases (mucositis/peri-implantitis) in HIV-1-infected individuals. In this prospective study, 13 HIV-1-infected individuals undergoing highly active antiretroviral therapy (with undetectable plasma HIV RNA levels, and CD4+ T cells > 350/mm ) were followed after implant placement, as well as 13 non-HIV-1-infected matched controls. Patients enrolled in this study were followed up to 120 months (mean = 40.6 months; standard deviation = 22.2; range 18 -120 months). Twenty-five implants were placed in pristine healed sites for each group and bone augmentation procedures, when needed, were done only for contour augmentation. Patients were enrolled in a strict periodontal/peri-implant supportive therapy protocol with three recalls per year. The two groups were compared regarding subject-level characteristics (age, gender, smoking, diabetes) and implant-level characteristics (marginal bone level, peri-implant health status). All the implants healed uneventfully and reached 100% survival rates (after at least 18 months) in both groups. There were no significant differences between groups for peri-implant diseases (mucositis/peri-implantitis) and for all subject-level co-variables (p > .05). Only the variables dental implant prosthesis type (DIPT) (p = .021, d = .86) and follow up (p = .011, d = .77) showed statistically significant differences between groups. The findings suggest that well-controlled HIV-1-infected individuals are eligible to undergo implant therapy, achieving survival and success rates comparable to non-HIV-1-infected controls.